2021
DOI: 10.1177/11206721211023314
|View full text |Cite
|
Sign up to set email alerts
|

The use of Ologen Collagen Matrix implants to treat ocular hypotony developing after trabeculectomy: A case series

Abstract: Purpose: Late hypotony is an undesirable and challenging complication of glaucoma surgery. We describe our use of the Ologen Collagen Matrix to treat late hypotony developing after trabeculectomy. Study design: A retrospective study performed at three eye surgery centers in Brazil. Participants: Eighteen patients who underwent 19 eye surgeries. Intervention: Subconjunctival Ologen was implanted at the trabeculectomy sites to treat over-filtering or leaking blebs in patients experiencing late hypotony after tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…40,167,171 The use of Ologen implant has been implemented to treat hypotony by a few retrospective studies with 63% to 87% success in IOP improvement without additional intervention and improved bleb morphology. 172,173 Encapsulated Bleb (Tenon Cyst) Encapsulated blebs are domeshaped elevations with thickened connective tissue and vascular engorgement at the sclerostomy site. They usually occur 2 to 8 weeks after surgery and are associated with elevations in IOP.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…40,167,171 The use of Ologen implant has been implemented to treat hypotony by a few retrospective studies with 63% to 87% success in IOP improvement without additional intervention and improved bleb morphology. 172,173 Encapsulated Bleb (Tenon Cyst) Encapsulated blebs are domeshaped elevations with thickened connective tissue and vascular engorgement at the sclerostomy site. They usually occur 2 to 8 weeks after surgery and are associated with elevations in IOP.…”
Section: Complicationsmentioning
confidence: 99%
“…More recently, studies have demonstrated improvement in vision and anatomical success after surgical intervention (similar approach to the repair of bleb leaks) for hypotony maculopathy 40,167,171 . The use of Ologen implant has been implemented to treat hypotony by a few retrospective studies with 63% to 87% success in IOP improvement without additional intervention and improved bleb morphology 172,173 …”
Section: Introductionmentioning
confidence: 99%